An immunoassay system to investigate epidemiology of Rocahepevirus ratti (rat hepatitis E virus) infection in humans - Jianwen Situ; Kelvin Hon-Yin Lo; Jian-Piao Cai; Zhiyu Li; Shusheng Wu; Estie Hon-Kiu Shun; Nicholas Foo-Siong Chew; James Yiu-Hung Tsoi; Gabriel Sze-Man Chan; Winson Hei-Man Chan; Cyril Chik-Yan Yip; Kong Hung Sze; et al. (JHEP Reports, 2023)
Background & Aims: Rat hepatitis E virus (Rocahepevirus ratti; HEV-C1) is an emerging cause of hepatitis E that is divergent from conventional human-infecting HEV variants (Paslahepevirus balayani; HEV-A). Validated serological assays for HEV-C1 are lacking. We aimed to develop a parallel enzymatic immunoassay (EIA) system that identifies individuals with HEV-C1 exposure. We also aimed to conduct the first HEV-C1 seroprevalence study in humans using this validated EIA system. Methods: Expressed HEV-A (HEV-A4 p239) and HEV-C1 (HEV-C1 p241) peptides were characterised. Blood samples were simultaneously tested in HEV-A4 p239 and HEV-C1 p241 IgG EIAs. An optical density (OD) cut-off-based interpretation algorithm for identifying samples seropositive for HEV-A or HEV-C1 was validated using RT-PCR-positive infection sera. This algorithm was used to measure HEV-C1 seroprevalence in 599 solid organ transplant recipients and 599 age-matched immunocompetent individuals. Results: Both peptides formed virus-like particles. When run in HEV-A4 p239 and HEV-C1 p241 EIAs, HEV-A and HEV-C1 RT-PCR-positive samples formed distinct clusters with minimal overlap in a two-dimensional plot of optical density values. The final EIA interpretation algorithm showed high agreement with RT-PCR results (Cohen’s κ = 0.959) and was able to differentiate HEV-A and HEV-C1 infection sera with an accuracy of 94.2% (95% CI: 85.8–98.4%). HEV-C1 IgG seroprevalence was 7/599 (1.2%) among solid organ transplant recipients and 4/599 (0.7%) among immunocompetent individuals. Five of 11 (45.5%) of these patients had history of transient hepatitis of unknown cause. Conclusions: HEV-C1 exposure was identified in 11/1198 (0.92%) individuals in Hong Kong indicating endemic exposure. This is the first estimate of HEV-C1 seroprevalence in humans. The parallel IgG EIA algorithm is a valuable tool for investigating epidemiology and risk factors for HEV-C1 infection. Impact and Implications: Rat hepatitis E virus has recently been discovered to infect humans, but antibody tests for this infection are lacking, making it difficult to gauge how common this infection is. We developed an antibody test algorithm that can identify individuals with past rat hepatitis E virus exposure. We used this algorithm to estimate rat hepatitis E exposure rates in humans in Hong Kong and found that approximately 1% of all tested people had been exposed to this virus previously.